From farm to market: Impacts of climate shocks on selected agricultural value chains in Ethiopia - Eleni Yitbarek; Wondimagegn Tesfaye (Research Network Sustainable Global Supply Chains, 2025)
While many of the studies to date have focused on the production end of the value chain-i.e., ways to help farmers grow more food, there is limited evidence regarding the impacts of climate shocks on the other stages of agricultural value chains. Recognizing that food security is not just an issue of production, there is now an emerging literature that attempts to link climate change with agricultural value chains. This study fills a critical gap in the literature by assessing the impacts of weather shocks not only on production but also on the post-production stages (storage and sales) across the agricultural value chains of four key commodities in Ethiopia: teff, maize, coffee, and dairy. The study addresses two questions: (i) How do weather shocks impact different stages of agricultural value chains? and (ii) are the negative effects of weather shocks on agricultural value chains heterogeneous by gender? We document that negative rainfall shocks drastically reduce maize and teff yields by about 40% and 37%, respectively, and significantly impact teff storage. Coffee yield is less affected by rainfall shocks, though its storage decreases by 28%. Temperature increases reduce yields for maize, teff, and coffee, with coffee also experiencing declines in storage and sales. For teff, temperature increases reduce the quantity stored by about 6.7% and sales by 18.5%. Similarly, an increase in temperature lowers coffee sales by 24.6%. Dairy production shows minimal sensitivity to both rainfall shocks and temperature variations. These effects vary by gender of the household head. For maize, temperature increases negatively affect yields more for male-headed households. Teff and coffee show varying impacts based on gender, with male-headed households experiencing more pronounced negative effects.
Keywords: Q12; Q54; Q18; Q13; J16; 330; climate shocks; value chains; agriculture; Ethiopia